The Contrasting Effects of Elevated CO2 on TYLCV Infection of Tomato Genotypes with and without the Resistance Gene, Mi-1.2 - Guo, Huijuan; Huang, Lichao; Sun, Yucheng; Guo, Honggang; Ge, Feng (Frontiers in Plant Science, 2016)
Elevated atmospheric CO2 typically enhances photosynthesis of C3 plants and alters primary and secondary metabolites in plant tissue. By modifying the defensive signaling pathways in host plants, elevated CO2 could potentially affect the interactions between plants, viruses, and insects that vector viruses. R gene-mediated resistance in plants represents an efficient and highly specific defense against pathogens and herbivorous insects. The current study determined the effect of elevated CO2 on tomato plants with and without the R gene Mi-1.2 and the subsequent effect on the severity of TYLCV and the performance of the vector, Bemisia tabaci. The results showed that elevated CO2 increased the biomass, plant height, and photosynthetic rate of both the wild-type and the Mi-1.2 genotype. Elevated CO2 decreased TYLCV disease incidence and severity for wild-type plants but had the opposite effect on Mi-1.2 plants whether the plants were artificially inoculated or inoculated via B. tabaci feeding. Elevated CO2 increased the salicylic acid (SA)-dependent signaling pathway on wild-type plants but decreased the SA signaling pathway on Mi-1.2 plants when infected by TYLCV. Elevated CO2 did not significantly affect B. tabaci fitness or the ability of viruliferous B. tabaci to transmit virus regardless of plant genotype. The results indicate that elevated CO2 increases the resistance of wild-type plants but decreases the resistance of Mi-1.2 plants against TYLCV, whether the plants are artificially inoculated or inoculated by the vector. Our results suggest that plant genotypes containing the R gene Mi-1.2 will be more vulnerable to TYLCV and perhaps to other plant viruses under elevated CO2 conditions.